Isoflavone aglycon produced by culture of soybean extracts with basidiomycetes and its anti-angiogenic activity - Miura, T. (Amino Up Chemical Co. Ltd., Sapporo (Japan)); Yuan, L; Sun, B; Fujii, H; Yoshida, M; Wakame, K; Kosuna, K (Bioscience, biotechnology, and biochemistry, 2002)
Soybean extracts (SBE) containing isoflavone glycosides were cultured with Ganoderma lucidum mycelia producing β-glucosidase. The anti-angiogenic effects of the cultivated product, containing rich in genistein, named GCP (genistein combined polysaccharide), were assessed with chick chorioallantoic membranes (CAM) and a mouse dorsal air-sac model. β-Glucosidase produced by the mycelia converted the isoflavone glycosides into aglycons. A test of volunteers showed that serum concentrations of genistein in the subjects treated with GCP (n=4) at 3 h after administration were significantly higher than those in the subjects treated with SBE (n=4). GCP inhibited angiogenesis in CAM, and the activity of GCP was greater than that of SBE. GCP inhibited the formation of new vessels induced by colon carcinoma cells in vivo.